Diversity and Antimicrobial Activities of Actinobacteria Isolated from Tropical Mangrove Sediments in Malaysia. (5th August 2014) - Lee, Learn-Han; Zainal, Nurullhudda; Azman, Adzzie-Shazleen; Eng, Shu-Kee; Goh, Bey-Hing; Yin, Wai-Fong; Ab Mutalib, Nurul-Syakima; Chan, Kok-Gan
Abstract : The aim of this study was to isolate and identify Actinobacteria from Malaysia mangrove forest and screen them for production of antimicrobial secondary metabolites. Eighty-seven isolates were isolated from soil samples collected at 4 different sites. This is the first report to describe the isolation of Streptomyces, Mycobacterium, Leifsonia, Microbacterium, Sinomonas, Nocardia, Terrabacter, Streptacidiphilus, Micromonospora, Gordonia, and Nocardioides from mangrove in east coast of Malaysia. Of 87 isolates, at least 5 isolates are considered as putative novel taxa. Nine Streptomyces sp. isolates were producing potent antimicrobial secondary metabolites, indicating that Streptomyces isolates are providing high quality metabolites for drug discovery purposes. The discovery of a novel species, Streptomyces pluripotens sp. nov. MUSC 135 T that produced potent secondary metabolites inhibiting the growth of MRSA, had provided promising metabolites for drug discovery research. The biosynthetic potential of 87 isolates was investigated by the detection of polyketide synthetase (PKS) and nonribosomal polyketide synthetase (NRPS) genes, the hallmarks of secondary metabolites production. Results showed that many isolates were positive for PKS-I (19.5%), PKS-II (42.5%), and NRPS (5.7%) genes, indicating that mangrove Actinobacteria have significant biosynthetic potential. Our results highlighted that mangrove environment represented a rich reservoir for isolation of Actinobacteria, which are potential sources for discovery of antimicrobial secondary metabolites.